Perancangan Sistem Web untuk Hafalan Tahfidz menggunakan Metode Extreme Programming pada Pondok Pesantren Raudhatul Ulum - Angga Pranata; Savitri (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
The advancement of information technology has become an essential requirement for educational institutions in managing data effectively. Pondok Pesantren Raudhatul Ulum in Lebak Regency still applies a manual system for managing students’ tahfidz memorization data, which results in inaccurate records, delays in information delivery, and difficulties in data organization and reporting. This study aims to develop a web-based information system for managing tahfidz memorization data to improve efficiency and data accuracy. The system was developed using the Extreme Programming (XP) method, with testing conducted through Black Box and White Box techniques. The results indicate that the proposed system facilitates faster, more structured, and accurate processes of recording, managing, and reporting tahfidz memorization data, while reducing errors commonly found in manual systems.